Government of India Websites: A Study - Walia, Paramjeet K.; Kaur, Prabhjeet (DESIDOC Journal of Library & Information Technology, 2010)
Ministries of Government of India have hosted their own websites across the World Wide Web so as to provide the world a view of the functioning of the Indian Government. It is essential these have to be up to the mark to represent the nation in an appropriate manner. But, despite this scale of involvement, there has been relatively little analysis of contents and visibility of these websites. This study highlights the importance of online government information in India and shows how far these websites have been able to make an impact on the society. The paper aims to examine the websites for their linking and content presence, and also to find out their web impact factor. The research methodology adopted for the study is investigative in nature. It includes observation of the selected websites from different points of view like number of webpages, web impact factor, and number of rich files. Data analyses and interpretation show that for each of the indicator used in this study, there were a different set of websites which achieved the topmost ranks. The findings of this study highlights the standing of these websites against the average values and show that different ministries excelled from different points of view. DOI: 10.14429/djlit.30.454